Prognostic Impact of Human Papilloma Virus Infection on Cervical Cancer Patients Reflected by p16ink4a Expression: Single Institution Experience - Ismail, Rehab Maher; Gaballah, Ahmed; Salama, Ahmed Husseiny; Shakweer, Marwa Mosaad; Meckawy, Ghada Refaat; Mahmoud Faisal, Malames (Asian Pacific Journal of Cancer Biology, 2023)
Background: Human Papilloma virus (HPV) is the main cause of cervical cancer. Infection with HPV can be reflected by overexpression of p16ink4a. Aim of the study: we aimed at evaluating the expression of p16ink4a in cervical cancer patients and its prognostic significance. Patients and methods: This retrospective registry and follow up study was conducted on 95 women diagnosed with cervical cancer. After screening of patients presented to our hospitals; 50 patients were eligible for inclusion in the study. P16ink4a was assessed by immunohistochemistry on archived tumor’s samples and correlation with different epidemiological, clinical and pathological data was performed. Prognostic impact of P16ink4a on overall survival (OS) and event free survival (EFS) was evaluated. Results: Median age of patients was 55 years. The main presenting symptom was bleeding. Most of the patients presented with late FIGO staging 64% with stage IIIb and 10% with stage IIb. P16ink4a was positive in 80% of patients. Correlation between P16ink4a and different clinic-epidemiological data revealed positive significant correlation with tumor grade and tumor size (P values of 0.03 and 0.05 respectively). Considering the effect of p16ink4a expression and EFS and OS, our study failed to show any significant correlation. Conclusion: The late stage at presentation of our population encourages the need for national screening program. The main cause of cervical cancer is HPV reflected by positive P16 similar to international literature. In our study the failure to reach a significant correlation with survival may be due the small sample size.